Association of Maternal and Umbilical Cord Blood Lipid Parameters with Uterine and Fetal-Placental Blood Flow in Hypertensive and Normotensive Pregnancies - Hessami K; Kasraeian M; Asadi N; Vafaei H; Foroughinia L (Dove Medical Press, 2020)
Kamran Hessami,1,2 Maryam Kasraeian,2 Nasrin Asadi,2 Homeira Vafaei,2 Leila Foroughinia3 1Student Research Committee, Shiraz University of Medical Sciences, Shiraz, Iran; 2Maternal-Fetal Medicine Research Center, Shiraz University of Medical Sciences, Shiraz, Iran; 3Eastern Health, Box Hill Hospital, FRANZCOG, Box Hill, Victoria, AustraliaCorrespondence: Kamran HessamiMaternal-Fetal Medicine (Perinatology) Research Center, Hafez Hospital, Chamran Ave, Shiraz, IranTel +98-71-36128257Fax +98-71-362128257Email hessamikamran@gmail.comPurpose: There is a growing evidence suggesting that hypertensive disorders of pregnancy (HDP), especially preeclampsia, are associated with an increased risk of cardiometabolic disease for both mother and child later in life. The objective of this study was to determine the association of maternal and umbilical cord blood (UCB) lipid profiles with uterine and fetal-placental blood flow at the third trimester of pregnancy.Patients and Methods: A total of  1,135 women were prospectively followed through pregnancy and data for 812 mother-newborn pairs, including 170 HDP ‎developed subjects and ‎ 642 ‎normotensive subjects were analyzed at the end of the study. Maternal serum and UCB triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and non-HDL-C levels were compared between HDP and normotensive groups; moreover, the association between lipid parameters and abnormal pulsatility indices (PIs) of uterine (UtA), umbilical (UA), and middle cerebral (MCA) arteries was evaluated with multivariate regression analysis models. The same analyses were carried out on subgroups of HDP (preeclampsia vs gestational hypertension).Results: The mean TG, TC, LDL-C, and non-HDL-C levels were significantly higher in mother-newborn pairs of the HDP group compared to the normotensive group. In the HDP group, maternal TG and non-HDL-C levels were shown to have a significant association with abnormal UtA-PI (p< 0.001 and p=0.039, respectively). We also found a positive significant association of fetal hypertriglyceridemia with abnormal UA-PI and MCA-PI in the HDP group (p=0.042 and p=0.021, respectively). However, no such associations were observed in normotensive mother-newborn pairs. Similar trends were observed in preeclamptic subjects after subgroup analysis.Conclusion: Maternal TG and non-HDL-C levels as well as fetal TG level are significantly associated with disturbed uterine and fetal-placental blood flow in HDP.Keywords: preeclampsia, gestational hypertension, uterine artery, umbilical artery, middle cerebral artery, lipid